Kualitas Pelayanan Inovasi Samsat dalam Meningkatkan Aksesibilitas Wajib Pajak di Kota Gorontalo - Miftah Revalina Rahim; Sri Yulianty Mozin; Muchtar Ahmad (Presidensial: Jurnal Hukum, Administrasi Negara, dan Kebijakan Publik, 2026)
This study analyzes the service quality of various Samsat service innovations, such as Mobile Samsat, Drive-Thru Samsat, Samsat Delivery, and Warkop Samsat, which have been developed to make it easier for the public to fulfill their motor vehicle tax payment obligations. However, the implementation of these innovations still faces various obstacles that may affect the ease of access to services for taxpayers. The study employed a qualitative approach with a descriptive method. The data were gathered through observations, in-depth interviews, and documentation, then analyzed using an interactive approach that included data collection, data reduction, data display, and conclusion formulation. results show that the service quality of Samsat innovations has been fairly good based on the dimensions of tangibles, reliability, responsiveness, assurance, and empathy. Various service innovations have been able to provide convenience, speed, and comfort for taxpayers in accessing tax services. Nevertheless, several obstacles were still identified, including network disruptions, limited facilities in off-site services, and a lack of public understanding. Therefore, improvements in technological infrastructure, supporting facilities, and the socialization of innovative services are needed to strengthen the accessibility and effectiveness of tax services in Gorontalo City.